STRATEGI PENYIARAN RADIO NEBULA 101FM DALAM MENJAGA EKSISTENSI DI KALANGAN PENDENGAR - Irnadi, Muhammad Agung; Zainuddin, Sumarni; Yusaputra, Muhammad Isa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2019)
This research aims to determine the strategy of broadcasting Nebula 101 fm radio in maintaining its existence among listeners. The writer uses descriptive research. Informants were selected by purposive sampling method. The informants selected were Agusta Sri Astuti (senior announcer at Radio Nebula 101Fm), Nana Rachman (junior announcer at Radio Nebula 101 Fm), and Ronny Rotty (Broadcast Manager at Radio Nebula 101 Fm). Data collection methods used are observation and interviews. The process of data analysis through qualitative data analysis methods. From the results of the research, it is known that in radio broadcasts, several steps need to be taken to maintain the continuity of the radio to last a long time and also the listeners of the radio feel comfortable to continue listening to the radio. Nebula FM is 25 years old, but still has an existence among its listeners. Radio implements strategies in the form of (1) Radio Nebula's management does not make Radio Nebula programs on a regular basis, but goes through the planning process and survey process to Nebula listeners, (2) One program has its own listeners, so Radio Nebula knows who the listeners are and that useful for making adlips for advertisements, (3) Radio Nebula adjusts the materials that must be brought on certain programs and the songs played must also be adjusted to the listener's mood at certain hours, (4) Programs that is on Radio Nebula, mostly old-school programming, but designed and presented differently. (5) The classification of existing programs makes radio has a diverse audience mass. Radio Nebula always strives to be able to maintain audiences and make interesting programs so that listeners are not easily left out.